Fabricating ceramic components with water dissolvable support structures by the Ceramic On-Demand Extrusion process. Issue 1 (2017) - Li, Wenbin; Ghazanfari, Amir; McMillen, Devin; Leu, Ming C.; Hilmas, Gregory E.; Watts, Jeremy
Abstract: This paper describes a further development of the novel Ceramic On-Demand Extrusion (CODE) process, with focus on fabricating ceramic components that have external/internal features and cannot be fabricated without the use of support structures. The minimum angle of a wedge-shaped part that can be fabricated using Al2 O3 (alumina) paste without a support structure is first determined. An inorganic sacrificial material, CaCO3 (calcium carbonate), is then identified for building support structures. After fabrication the green part is dried and then sintered. During sintering, the main material densifies, while the sacrificial material decomposes and is then dissolved in water or acid. Sample parts are fabricated and evaluated.